Computer-Guided Surgery in Implantology: Review of Basic Concepts - de Almeida, Erika Oliveira [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; Margonar, Rogerio; Rocha, Eduardo Passos [UNESP]; Freitas, Amilcar Chagas [UNESP]; Anchieta, Rodolfo Bruniera [UNESP] (Lippincott Williams & Wilkins, 2010)
The aim of the present study was to conduct a critical literature review about the technique of computer-guided surgery in implantology to highlight the indications, purposes, immediate loading of implants and complications, protocol of fabrication, and functioning of virtual planning software. This literature review was based on OLDMEDLINE and MEDLINE databases from 2002 to 2010 using the key words "computer-guided surgery" and "implant-supported prosthesis." Thirty-four studies regarding this topic were found. According to the literature review, it was concluded that the computer-assisted surgery is an excellent treatment alternative for patients with appropriate bone quantity for implant insertion in complete and partially edentulous arches. The Procera Nobel Guide software (Nobel Biocare) was the most common software used by the authors. In addition, the flapless surgery is advantageous for positioning of implants but with accurate indication. Although the computer-guided surgery may be helpful for virtual planning of cases with severe bone resorption, the conventional surgical technique is more appropriate. The surgical guide is important for insertion of the implants regardless of the surgical technique, and the success of immediate loading after computer-guided surgery depends on the accuracy of clinical and/or laboratorial steps.
Keywords: Prostheses and implants; tomography; osseointegration